2013
DOI: 10.1371/journal.pone.0081493
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of a Novel Frameshift Mutation in the C-terminus of the Nav1.5 Channel Underlying a Brugada Syndrome with Variable Expression in a Spanish Family

Abstract: IntroductionWe functionally analyzed a frameshift mutation in the SCN5A gene encoding cardiac Na+ channels (Nav1.5) found in a proband with repeated episodes of ventricular fibrillation who presented bradycardia and paroxysmal atrial fibrillation. Seven relatives also carry the mutation and showed a Brugada syndrome with an incomplete and variable expression. The mutation (p.D1816VfsX7) resulted in a severe truncation (201 residues) of the Nav1.5 C-terminus. Methods and ResultsWild-type (WT) and mutated Nav1.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 34 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…In 1 of these 3 cases, co-segregation with the pathogenic variant p.D1816Vfs in SCN5A was confirmed in 7 carrier relatives ( Figure 3A). This mutation causes severe truncation (201 residues) of the C-terminus of Nav1.5 and the functional analysis revealed a marked reduction in channel trafficking towards the membrane and in sodium current density compared with non-mutated channels (WT) 18 . In another case, despite a negative adrenaline test in the proband, who had severe neurological damage, an upper limit of normal QTc was detected in a firstdegree relative.…”
Section: Resultsmentioning
confidence: 99%
“…In 1 of these 3 cases, co-segregation with the pathogenic variant p.D1816Vfs in SCN5A was confirmed in 7 carrier relatives ( Figure 3A). This mutation causes severe truncation (201 residues) of the C-terminus of Nav1.5 and the functional analysis revealed a marked reduction in channel trafficking towards the membrane and in sodium current density compared with non-mutated channels (WT) 18 . In another case, despite a negative adrenaline test in the proband, who had severe neurological damage, an upper limit of normal QTc was detected in a firstdegree relative.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the density of Na + currrent was reduced to ∼60% of the WT Na + current density, and the voltage dependence of inactivation was also shifted towards negative voltages compared to the WT channel. Some research showed that when co-expressing trafficking-deficient BrS SCN5A mutations with WT Na v 1.5 channel (0.5:0.5 in ratio) in heterologous expression systems, it is observed that the Na + current was reduced by about 50% compared to the Na + current produced by expressing only WT Na v 1.5 channel [33][34][35]. Such reduction of Na + current is due to the haploinsufficiency of WT Na v 1.5 channel.…”
Section: Discussionmentioning
confidence: 99%
“…However, Olson and colleagues identified the first SCN5A missense mutation that was associated with several cardiac phenotypes including AF [ 76 ]. Subsequently, multiple mutations in SCN5A gene have been identified in patients with AF, alone [ 77 , 78 , 79 , 80 , 81 ] or with combined cardiac conditions [ 76 , 82 , 83 , 84 , 85 , 86 ]. Several variants of SCNA5 have been reported in patients with common polygenic AF as well [ 87 ].…”
Section: Genetics Of Atrial Fibrillationmentioning
confidence: 99%